(untitled) (Kronika Bydgoska, 2018)
The principal materials for studies on the shaping and functioning of the urban-architectural organism include technical documentation, cartography and other documents collected in archives. Sometimes, however, these sources are incomplete. Therefore, this article has been written based on searches in Bydgoszcz newspapers, which purpose is to focus attention on analytical usefulness of the press and thus its importance for researchers involved in studying the local history, as well as history of architecture and urban planning. The article also mentions selected information on building matters and celebrations taking place in the city of Bydgoszcz, taken from press advertisements, articles and newspapers published during the times of the Prussian Partition. These examples show a broad spectrum o f news contained in newspapers, which are still underestimated as a source of information providing the date of construction and builders of individual structures, describing their architecture, as well as development and functioning of public spaces, focusing in particular on the most exclusive neighborhoods.